LIDAR+disturbance accommodating control of wind turbine for blade load mitigation - Pham, Tien Hung (2015)
Robust controllers for wind turbine have always been a focused topic of study in the wind turbine community. The reason is chiefly due to the controller’s capability to significantly elevate load on the wind turbine without any hardware changes. Recently, the remote sensing wind technology, LIDAR (Light and Radar), is found to be economically viable to the wind turbine community. Therefore, a new challenge is posed to the wind turbine maker: how to effectively take advantage of this information to mitigate load. The most notable LIDAR based controllers at the moment use the measurements of the upcoming wind field to pre-actuate the blade, thus achieving better load reduction. However, these controllers have their own shortcomings. As a new proposal, this project proposes a novel controller design, LIDAR+DAC, that doesn’t employ a wind-previewing tactic. Thus, it can avoid the limitations of the wind-preview controllers. Moreover, simulations with full degree of freedom wind turbine using FAST show that the controller is capable of better load reduction in the range of 20% as compared to standard LIDAR based controllers.